The Effect of Tiktok Platform on Reading Habits of MA Nurul Ichsan Students - Jennah, Sofiyatul; Sholah, Hanif Maulaniam (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to examine the effect of using the TikTok platform on the reading habits of MA Nurul Ichsan students. The background of this research is the increasing popularity of social media, which potentially shifts students’ traditional reading interest. The study employed a descriptive method with data collected through questionnaires and observations involving students of grades X, XI, and XII. The findings reveal that the majority of students experienced a decline in reading interest after actively using TikTok. A total of 90.4% of respondents reported decreased reading motivation, with 57.1% rarely reading books outside school hours, and 60% facing concentration difficulties after using the application. Furthermore, 80% of students preferred entertainment content over educational content. Although 5% of students felt motivated to seek reading material from TikTok content, the negative effects remain more dominant. This research highlights the importance of the roles of teachers and parents in guiding students to use social media wisely and in fostering consistent reading habits.